2019
DOI: 10.1002/jobm.201800676
|View full text |Cite
|
Sign up to set email alerts
|

Identification of two two‐component signal transduction mutants with enhanced sucrose biosynthesis in Synechococcus elongatus PCC 7942

Abstract: Metabolic engineering of the freshwater cyanobacterium Synechococcus elongatus PCC 7942 (Syn7942), synthesizing sucrose as the only compatible solute upon salt stress, has greatly improved its sucrose productivity. However, the signaling and regulatory mechanisms of this physiological process are still unknown. To know more about these aspects, a library of inactivation mutants for all 44 predicted signal transduction genes of Syn7942 was constructed. By evaluating sucrose production, two two-component signal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 50 publications
(76 reference statements)
0
4
0
Order By: Relevance
“…In this context, a couple of studies have reported promising improvements in sucrose secretion rates by altering cyanobacterial two-component regulatory proteins, although the specific mechanisms remain uncertain. In a screen of all two-component regulatory factors in S. elongatus PCC 7942, Qiao and colleagues identified genes indirectly linked to sucrose productivity, glycogen accumulation, and photosynthetic activity ( Qiao et al, 2019 ). The partial deletion of ManR, a protein that plays a regulatory role in Mn 2+ uptake ( Ogawa et al, 2002 ; Yamaguchi et al, 2002 ; Zorina et al, 2016 ), increased sucrose by 60%, a complete knockout of Synpcc7942_1125 increased sucrose by 41% ( Qiao et al, 2019 ; Table 1 ).…”
Section: Engineering Cyanobacteria To Produce Sucrosementioning
confidence: 99%
See 1 more Smart Citation
“…In this context, a couple of studies have reported promising improvements in sucrose secretion rates by altering cyanobacterial two-component regulatory proteins, although the specific mechanisms remain uncertain. In a screen of all two-component regulatory factors in S. elongatus PCC 7942, Qiao and colleagues identified genes indirectly linked to sucrose productivity, glycogen accumulation, and photosynthetic activity ( Qiao et al, 2019 ). The partial deletion of ManR, a protein that plays a regulatory role in Mn 2+ uptake ( Ogawa et al, 2002 ; Yamaguchi et al, 2002 ; Zorina et al, 2016 ), increased sucrose by 60%, a complete knockout of Synpcc7942_1125 increased sucrose by 41% ( Qiao et al, 2019 ; Table 1 ).…”
Section: Engineering Cyanobacteria To Produce Sucrosementioning
confidence: 99%
“…In a screen of all two-component regulatory factors in S. elongatus PCC 7942, Qiao and colleagues identified genes indirectly linked to sucrose productivity, glycogen accumulation, and photosynthetic activity ( Qiao et al, 2019 ). The partial deletion of ManR, a protein that plays a regulatory role in Mn 2+ uptake ( Ogawa et al, 2002 ; Yamaguchi et al, 2002 ; Zorina et al, 2016 ), increased sucrose by 60%, a complete knockout of Synpcc7942_1125 increased sucrose by 41% ( Qiao et al, 2019 ; Table 1 ). In a separate study, overexpression of the two-component protein regulator of phycobilisome assembly B ( rpaB ) reproduced a growth-arrest phenotype in S. elongatus PCC 7942 ( Moronta-Barrios et al, 2013 ), and increased sucrose secretion in a cscB -expressing background ( Abramson et al, 2018 ; Table 1 ).…”
Section: Engineering Cyanobacteria To Produce Sucrosementioning
confidence: 99%
“…The extraction and determination of intracellular compatible solutes (mainly GG) of Syn6803 were performed as previously described (Qiao et al 2019 ). The same procedure was applied to Marinobacter .…”
Section: Methodsmentioning
confidence: 99%
“…RNA was extracted by using a MiniBEST plant RNA extraction kit (TaKaRa Bio, Shiga, Japan) and treated with DNase I (TaKaRa Bio). Reverse transcription of RNA was performed as previously described (55). Equal amounts of cDNA were used for further DNA amplification by PCR by using the primer pairs RT-sps-F/RT-sps-R and RT-rnpB-F/RT-rnpB-R (Table S2).…”
Section: Methodsmentioning
confidence: 99%